Sex-Linked Differences in Cardiac Atrophy After Heterotopic Heart Transplantation: No Direct Relation to the Actions of Sex Steroid Hormones - Kolesár, D M; Kujal, P; Mrázová, I; Pokorný, M; Škaroupková, P; Vaňourková, Z; Sadowski, J; Červenka, L; Netuka, I (Physiological research, 2024)
An important complication of prolonged support of the left ventricle with an assist device when implanted in patients with heart failure is unloading-induced cardiac atrophy. Our recent study suggested that sex-linked differences in the development of atrophy induced by heterotopic heart transplantation (HTX) do exist, however, the role of the environmental conditions dependent on plasma concentrations of sex hormones remains elusive. We aimed to compare the course of HTX-induced cardiac atrophy in male and female rats after gonadectomy with substitution of steroid hormones of the opposite sex. In a separate series of experiments, we evaluated the course of unloading-induced cardiac atrophy in the female heart transplanted into a male recipient and vice versa. Cardiac atrophy was assessed as the ratio of the transplanted heart weight to native heart weight (HW), which was determined 14 days after HTX. In female rats, studied in both experimental variants, HTx resulted in significantly smaller decreases in whole HW when compared to those observed in male rats exposed to the same experimental conditions (-9 ± 1 and - 11 + 1 vs. -44 ± 2 and -42 ± 2 %, p?0.05 in both cases). The dynamic of changes in left and right ventricle was similar as in the whole HW. Our results show that the process of unloading-induced cardiac atrophy exhibits important sex-linked differences and that attenuation of this process in female rats cannot be simply ascribed to the protective effects of estradiol or to the absence of deleterious actions of testosterone. Keywords: Cardiac atrophy, Sex differences, Gonadectomy, Hormonal substitution, Heterotopic heart transplantation, Mechanical heart unloading.
Keywords: transplantace srdce; Atrophy; estradiol; Female; krysa rodu Rattus; Heart Transplantation; pohlavní steroidní hormony; zvířata; potkani Wistar; atrofie; heterotopická transplantace; ženské pohlaví; Transplantation, Heterotopic; Rats, Wistar; Male; Testosterone; Estradiol; Heart; Sex Characteristics; Gonadal Steroid Hormones; pohlavní dimorfismus; Rats; Animals; mužské pohlaví; testosteron; srdce